Microbial Infectious Disease: A Mini Review - Priyanka Debta1, Santosh Kumar Swain2, Md. Tariq Soyab3, Mahesh Chandra Sahu4, Smarita Lenka5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In the 21st century where science and its technology have revolutionized the world, there has been also aremarkable increase in the infectious diseases which have disastrously affected mankind. From the past whenmillions of people die due to chickenpox and measles in America till today when a virus like the SARS,Coronavirus (COVID 19) has challenged the world, which is a highly infectious disease. Infectious diseasereports the main cause of death in this global world. Despite high equipment facilities and technology, thistype of disease has regularly challenged the global scenario. Infectious diseases are particularly importantcauses of death among the people who are elderly, immunocompromised, already having a chronic diseaseand also to whom who are suffering from malnutrition. The article focuses on the mechanisms by which theinfectious agents cause pathology, various routes of infection and also throws light on the different microbialagents which are causing various infectious diseases.